2012
DOI: 10.1007/s11357-012-9477-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired secretion of interferons by dendritic cells from aged subjects to influenza

Abstract: Increased susceptibility to respiratory infections such as influenza is the hallmark of advancing age. The mechanisms underlying the impaired immune response to influenza are not well understood. In the present study, we have investigated the effect of advancing age on dendritic cell (DC) function because they are critical in generating robust antiviral responses. Our results indicate that monocyte derived DCs from the aged are impaired in their capacity to secrete interferon (IFN)-I in response to influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 76 publications
(81 reference statements)
3
56
0
1
Order By: Relevance
“…12 These include their capacity to phagocytose antigens, 13 migration to lymph nodes, 13 response to pathogens, 14,15 and impaired secretion of certain key cytokines such as IFN-α and IFN-l. 1416 Furthermore, DCs from the elderly display increased basal level of activation as evidenced by increased activation of nuclear factor κB, 17 which has a major role in the secretion of pro-inflammatory mediators by DCs. Increased basal level nuclear factor κB activation in aged DCs may result in an enhanced secretion of various molecules under steady state, in the absence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…12 These include their capacity to phagocytose antigens, 13 migration to lymph nodes, 13 response to pathogens, 14,15 and impaired secretion of certain key cytokines such as IFN-α and IFN-l. 1416 Furthermore, DCs from the elderly display increased basal level of activation as evidenced by increased activation of nuclear factor κB, 17 which has a major role in the secretion of pro-inflammatory mediators by DCs. Increased basal level nuclear factor κB activation in aged DCs may result in an enhanced secretion of various molecules under steady state, in the absence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the production of TNF-α is a determining factor in the dC-mediated Cd8+ T cell response against influenza (liu et al 2012). In addition, a comparison of the antigenpresenting capacity of aged plasmacytoid dendritic cell (PDC) with young PDC revealed that PDC from aged subjects displays reduced capacity to induce proliferation and IFN-γ secretion in Cd4+ and CD8+ T cells as compared with PDC from young subjects (Sridharan et al 2011, Prakash et al 2013). …”
Section: Skin and Mucousmentioning
confidence: 99%
“…Impaired IFN-I and -III production by pDCs may be linked to an alteration in IRF-7 phosphorylation, which is impaired in DCs of aged subjects but increased in young subjects (Sridharan et al, 2011). Recent findings reveal that the age-associated reduction in the ability of monocyte derived DCs to produce IFN-I and III in response to influenza virus is linked to alterations in chromatin structure (Prakash et al, 2012). Surface expression of CD54 and MHC II that improve contact between APCs and T cells is comparable between young and elderly subjects with increases observed upon exposure to influenza vaccine and in the production of IL-12 and TNF-α (SaurweinTeissl et al, 1998).…”
Section: Cytokine Expression By Dcs During Ageingmentioning
confidence: 99%